Characterization of Monkeypox virus dissemination in the black-tailed prairie dog (Cynomys ludovicianus) through in vivo bioluminescent imaging. - Zachary P Weiner; Johanna S Salzer; Elizabeth LeMasters; James A Ellison; Ashley V Kondas; Clint N Morgan; Jeffery B Doty; Brock E Martin; Panayampalli Subbian Satheshkumar; Victoria A Olson; Christina L Hutson (PLoS ONE, 2019)
Monkeypox virus (MPXV) is a member of the genus Orthopoxvirus, endemic in Central and West Africa. This viral zoonosis was introduced into the United States in 2003 via African rodents imported for the pet trade and caused 37 human cases, all linked to exposure to MPXV-infected black-tailed prairie dogs (Cynomys ludovicianus). Prairie dogs have since become a useful model of MPXV disease, utilized for testing of potential medical countermeasures. In this study, we used recombinant MPXV containing the firefly luciferase gene (luc) and in vivo imaging technology to characterize MPXV pathogenesis in the black-tailed prairie dog in real time. West African (WA) MPXV could be visualized using in vivo imaging in the nose, lymph nodes, intestines, heart, lung, kidneys, and liver as early as day 6 post infection (p.i.). By day 9 p.i., lesions became visible on the skin and in some cases in the spleen. After day 9 p.i., luminescent signal representing MPXV replication either increased, indicating a progression to what would be a fatal infection, or decreased as infection was resolved. Use of recombinant luc+ MPXV allowed for a greater understanding of how MPXV disseminates throughout the body in prairie dogs during the course of infection. This technology will be used to reduce the number of animals required in future pathogenesis studies as well as aid in determining the effectiveness of potential medical countermeasures.